The Characteristics of the Skin Physiological Parameters and Facial Microbiome of “Ideal Skin” in Shanghai Women - Ma L; Niu Y; Yuan C; Bai T; Yang S; Wang M; Li Y; Shao L (Dove Medical Press, 2023)
Laiji Ma,1,2 Yujie Niu,1,2 Chunying Yuan,3 Tianming Bai,3 Suzhen Yang,3 Man Wang,4 Yan Li,3 Li Shao1 1School of Perfume and Aroma Technology, Shanghai Institute of Technology, Shanghai, People's Republic of China; 2The Oriental Beauty Valley Research Institute, Shanghai Institute of Technology, Shanghai, People's Republic of China; 3R&D Innovation Center, Shandong Freda Biotech Co., Ltd., Jinan, Shandong, People's Republic of China; 4Department of Nutrition, Shanghai Jiao Tong University Affiliated Sixth People's Hospital South Campus, Shanghai, People's Republic of ChinaCorrespondence: Li Shao, School of Perfume and Aroma Technology, Shanghai Institute of Technology, No. 100, Haiquan Road, Fengxian District, Shanghai, 201418, People's Republic of China, Email teamo-lily@163.com Yan Li, R&D Innovation Center, Shandong Freda Biotech Co., Ltd, No. 888, Xinluo Street, Lixia District, Jinan, Shandong, 250101, People's Republic of China, Email 378097042@qq.comPurpose: Everyone pursues perfect skin, but there exist significant differences between cultures, and no commonly accepted standards have been established. Therefore, our study attempted to define the "ideal skin" of oriental women and analyze the relationship between different skin physiological parameters and microbiomes.Patients and Methods: Based on our customized grading standard, the VISIA CR photos of 111 young women aged from 18 to 25 in Shanghai were collected and scored by the severity of pores, acne, spots, and wrinkles. The volunteers were then divided into "ideal skin" (W1), "normal skin" (W2), and "undesirable skin" (W3) groups. The physiological parameters of facial skin were measured by non-invasive instrumental methods, and the skin microbiome was analyzed by 16S rRNA and ITS high-throughput sequencing.Results: From "ideal skin" to "undesirable skin", the skin physiological parameters, α-diversity, and composition of the facial microbiome showed noticeable regular changes. Compared with the "normal skin" (W2) and "undesirable skin" (W3), the "ideal skin" (W1) group had lower sebum content, TEWL, melanin, hemoglobin, and roughness but higher hydration content and skin pH value. Furthermore, the Shannon index of skin bacteria was significantly increased in W1 (P = 0.004), suggesting that the ideal skin had higher species diversity. From W1 to W3, the species composition was changed significantly. The abundance of Actinobacteria was increased, while Proteobacteria and Bacteroidetes were decreased. Correspondingly, the abundances of lipophilic Propionibacterium and Malassezia were increased, while the abundances of Stenotrophomonas, Pseudomonas, Ralstonia, and Streptococcus, were significantly decreased. Additionally, Spearman correlation analysis revealed strong correlations between the physiological parameters and the microbiota. Notably, the Shannon index of skin bacteria was significantly positively correlated with skin hydration (P = 0.03) but negatively correlated with the abundance of Cutibacterium (P = 0.000), hemoglobin content (P = 0.025), and sebum content (P = 0.5). Therefore, the skin hydration content and the abundance of Cutibacterium played an important role in maintaining the α-diversity and skin homeostasis.Conclusion: Ideal skin had better water-oil balance and barrier function, higher microbial diversity, and more reasonable species distribution. Therefore, daily skincare needs to control skin oil and maintain skin microecological balance to achieve ideal skin conditions for young women aged 18- 25 years old.Keywords: Shanghai women, ideal skin, definition, physiological parameters, skin microbiome